MODEL OF ENSURING INTERNATIONAL COMPETITIVENESS OF UKRAINIAN PROCESSING ENTERPRISES IN MODERN CONDITION - KHACHATRYAN, Valentyna; STRATIICHUK, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the dynamics of the share of processing enterprises in Ukraine in the context of a full-scale war, which is critically important for understanding the sustainability of the national economy. The analysis identified key risks for enterprises that create add value, including disruption of logistics, loss of production capacity, migration of skilled labor, and limited access to financing. The sharp decline in the share of the processing industry studied, the decline is a deep decline in the industrial sector due to the war. Given the identified risks, it is processing enterprises that need to improve the management process in the context of leveling external risks and finding sources of increasing the efficiency of their activities. Improving the business management model and ensuring competitiveness in the global market is a significant contribution to improving the activities of the processing business in Ukraine under martial law. To counter these threats and ensure sustainable development, elements of a model for ensuring international competitiveness for Ukrainian enterprises in the processing industry are proposed. This complex model integrates three interconnected subsystems: production, sales and personnel. Within each subsystem, the main factors of influence on international competitiveness identified and substantiated, such as innovation, quality, market diversification and personnel qualifications. For each factor, specific methods of improving the impact proposed, which implemented. The expected results of implementing the proposed methods include increasing operational efficiency, increasing export potential and strengthening the positions of Ukrainian products in world markets. All studied subsystems integrated into a holistic model of ensuring the international competitiveness of Ukrainian processing enterprises, which serves as a practical tool for forming anti-crisis and export-oriented strategies in the conditions of the war economy and post-war recovery.
Keywords: international competitiveness; processing enterprise; international activity; model of ensuring international competitiveness